2002
DOI: 10.1021/jo020299z
|View full text |Cite
|
Sign up to set email alerts
|

Arteminolides B, C, and D, New Inhibitors of Farnesyl Protein Transferase from Artemisia argyi

Abstract: Arteminolides B-D (2-4), new farnesyl protein transferase inhibitors, were isolated together with a known arteminolide A (1) and new regioisomers (5-7) of the compounds from the aerial parts of Artemisia argyi. Structures of these compounds were elucidated by spectroscopic methods and chemical conversion. Arteminolides inhibited the farnesyl protein transferase with IC(50) values of 0.7-1 microM, while the regioisomers 5-7 were inactive. In addition, it was proved that the exocyclic double bond of sesquiterpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…The chemical ingredients of moxa floss may lay the foundation for the effects of moxa smoke, such as flavones isolated from Artemisia argyi inhibiting proliferation of a couple of tumor cell lines [22] and Arteminolides B-D (2-4) isolated from Artemisia argyi inhibiting the farnesyl protein transferase [23]. Clinically, moxa floss with good quality has to be specially processed and preserved for a relatively long time.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical ingredients of moxa floss may lay the foundation for the effects of moxa smoke, such as flavones isolated from Artemisia argyi inhibiting proliferation of a couple of tumor cell lines [22] and Arteminolides B-D (2-4) isolated from Artemisia argyi inhibiting the farnesyl protein transferase [23]. Clinically, moxa floss with good quality has to be specially processed and preserved for a relatively long time.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, the biogenetic pathway of plagiospirolide A was proposed [101]; this pathway was supported by the synthesis featuring a Diels-Alder reaction of diplophyllolide A and diene 47 [102]. Biogenetically related adducts between an α-methylene butenolide and cyclopentadiene are plagiospirolide E [103], biennin C [104], arteminolide B [105], ornativolide A [106], artemisolide [107], and stolonilactone [108]. Cyclopentadiene dimers absinthin [109] and vielanin A [110] and guaiane sesquiterpene dimer [111] are also found.…”
Section: Cyclopentadiene Formation Derived From Dehydrogenationmentioning
confidence: 96%
“…Stem Anti-tumor, anti-platelet aggregation and anti-inflammation (Siripong et al 2006;Wu et al 1998;Punturee et al 2004) Annona squamosa Seed Cytotoxicity (Liaw et al 2008); anti-inflammation Goniothalamus amuyon Stem and root Cytotoxicity & anti-cancer (Lan et al 2003(Lan et al , 2006 Catharanthus roseus Stem Anti-cancer (van der Heijden et al 2004); antioxidant (Ferreres et al 2008) Emilia sonchifolia Stem Anti-inflammation and cytotoxicity (Muko and Ohiri 2000;Shylesh and Padikkala 2000) Artemisia argyi Stem Farnesyl protein transferase inhibitor (Lee et al 2002;Seo et al 2003) Ixeris chinensis Stem Antifebrile, antidotal, and analgesic effects (Zhang et al 2006) Euonymus spraguei Stem Not found…”
Section: Rhinacanthus Nasutusmentioning
confidence: 99%